High-efficiency electroplating process
By grinding, degreasing and eroding the substrate, combined with specific electroplating solution composition and process parameters, the problem of impurities on the surface of the substrate in electroplating affect the binding performance of the plating layer is solved, and an efficient and high-quality electroplating process is achieved.
Patent Information
- Application Number
- CN202411904123.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
In the existing electroplating process, impurities such as oil stains and oxide film on the surface of the substrate affect the bonding performance of the plating layer and the substrate, resulting in low electroplating efficiency and quality.
High-efficiency electroplating process is adopted, including grinding, oil removal and erosion treatment of the substrate, removing impurities and oxide films on the surface, and improving the quality and stability of the plating layer through specific electroplating solution composition and process parameters (such as current density, temperature, and plating time).
By removing impurities and oxide films on the surface of the substrate, the binding performance of the plating and the substrate and the quality of the plating are significantly improved, and the efficiency and product performance of electroplating are improved.
Smart Images

Figure BDA0005203964720000081 
Figure BDA0005203964720000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of electroplating, and in particular to a high-efficiency electroplating process. Background Art
[0002] Electroplating is the process of plating a thin layer of other metals or alloys on the metal surface using the principle of electrolytic electrolysis. It uses electrolytic action to make a layer of metal film adhere to the surface of metal or other material parts, thereby preventing the occurrence of metal oxidation, rust and other phenomena.
[0003] During electroplating, the plating metal or other insoluble material acts as the anode and the workpiece to be plated acts as the cathode. The cations of the plating metal are reduced on the surface of the workpiece to be plated to form a plating layer. However, in the current electroplating process, the surface of the electroplated substrate usually has residual oil, oxide film, etc., which affects the bonding performance between the electroplated layer and the substrate, and affects the efficiency of electroplating. Summary of the invention
[0004] In order to improve the efficiency and product performance of electroplating, the present application provides a high-efficiency electroplating process.
[0005] The present application provides a highly efficient electroplating process using the following technical solutions: A highly efficient electroplating process comprises the following steps: S1. Grinding the substrate to remove debris on the surface of the substrate to make the surface of the substrate smooth; S2, degreasing the polished substrate with a degreasing agent; S3, subjecting the deoiled substrate to an erosion treatment; S4, transferring the plating solution to an electroplating tank, heating the plating solution and maintaining a stable temperature under the condition of a constant temperature water bath, immersing the etched substrate in the plating solution, and connecting a power supply for electroplating; S5. After the electroplating is completed, the substrate is taken out, and the residual plating solution on the surface of the substrate is washed, and then dried, and a coating is obtained on the surface of the substrate, and the electroplating is completed; The plating solution includes electrolytes including nickel sulfate hexahydrate, cobalt sulfate heptahydrate and sodium hypophosphite.
[0006] By adopting the above technical scheme, after polishing the substrate, scratches, rust spots, etc. on the surface of the substrate can be removed, so that the surface of the substrate is smooth and flat, and the electroplating quality of the coating is further improved; after degreasing the substrate, the oil stains on the surface of the substrate can be removed, thereby promoting the bonding stability between the substrate and the coating, and further improving the quality of the coating; after etching the base layer, the oxide film and rust product adhesion on the surface of the substrate can be effectively removed, thereby further improving the bonding performance between the substrate and the coating, and making the coating adhesion more stable, thereby improving the efficiency of electroplating; in the present application, the electrolyte is prepared by combining a sulfate-chloride system to obtain a coating, and a Ni-Co-P coating can be obtained. The alloy coating has a metallic luster similar to that of stainless steel, and the coating has good bonding strength, wear resistance, corrosion resistance and hardness, and the quality of the prepared coating is improved, effectively improving the electroplating quality and electroplating efficiency.
[0007] Preferably, the mass ratio of the nickel sulfate hexahydrate, the cobalt sulfate heptahydrate and the sodium hypophosphite is (12.7-14.7):1:1.17.
[0008] By adopting the above technical solution, the mass ratio of nickel sulfate hexahydrate, cobalt sulfate heptahydrate and sodium hypophosphite is preferably within the above range, which can further improve the stability of the prepared electroplating layer.
[0009] Preferably, the current density is 2-3.5A / dm 2 .
[0010] By adopting the above technical solution, the current density during electroplating is preferably within the above range, which can further improve the stability of the prepared electroplating layer, and the surface of the prepared Ni-Co-P coating is flat and smooth, and the product quality is further improved.
[0011] Preferably, the electroplating temperature is 55-65°C.
[0012] By adopting the above technical solution, the electroplating temperature is preferably within the above range, which can increase the deposition rate of the coating, promote the formation of crystal nuclei, and discharge hydrogen in time, thereby effectively reducing the porosity of the coating and improving the hardness of the coating, thereby improving the stability of the coating and improving product quality.
[0013] Preferably, the electroplating time is 48-52 minutes.
[0014] By adopting the above technical solution, the electroplating time is preferably within the above range, so that the electroplated coating can evenly cover the surface of the substrate, thereby protecting the substrate and improving product preparation efficiency and quality.
[0015] Preferably, a complexing agent is further added to the electroplating solution, and the complexing agent includes trisodium citrate.
[0016] By adopting the above technical solution, the complexing agent can improve the coverage of the plating solution on the base layer and can further promote the dispersion performance of the plating solution. In the present application, trisodium citrate is used as a complexing agent, which can form a complex with both nickel ions and cobalt ions to enhance the polarization of the cathode electrode, thereby further improving the electroplating efficiency and the stability of the electroplated layer.
[0017] Preferably, a surfactant, thiourea and sodium propylene sulfonate are also added to the electroplating solution.
[0018] By adopting the above technical scheme, the surfactant can reduce the surface tension of the plating solution, thereby promoting the coating of the plating solution on the surface of the substrate, and at the same time, it can also promote the precipitation of hydrogen adsorbed on the cathode surface, so that the surface of the electroplated coating is smooth; after adding thiourea, the hardness and glossiness of the coating can be further improved, thereby improving the stability of the coating; after adding sodium propylene sulfonate, it can also promote the improvement of the hardness and glossiness of the coating, and the density of the coating is improved, so that the performance of the electroplated product is effectively improved.
[0019] Preferably, the concentration of the surfactant is 0.09-0.11 g / L, the concentration of the thiourea is 0.14-0.16 g / L, and the concentration of the sodium propylene sulfonate is 0.25-0.35 g / L.
[0020] By adopting the above technical solution, preferably the concentration of the surfactant, the concentration of thiourea, and the concentration of sodium propylene sulfonate are within the above ranges, which can further improve the stability of the electroplated coating and the product quality.
[0021] Preferably, the surfactant comprises sodium lauryl sulfate.
[0022] By adopting the above technical solution, sodium dodecyl sulfate can reduce the holes in the coating, thereby improving the overall stability of the coating.
[0023] Preferably, the degreasing agent comprises triammonium citrate, sodium silicate, sodium carbonate and an emulsifier.
[0024] By adopting the above technical solution, the above components are compounded and then chemically degreased, which can effectively remove oil stains on the surface of the substrate, thereby keeping the surface of the substrate smooth and tidy, and can efficiently and gently remove oil stains, so as to further improve the bonding effect between the coating and the substrate.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application polishes the surface of the substrate to remove scratches, rust spots, etc. on the surface of the substrate, thereby improving the flatness of the surface of the substrate so that the coating can be better combined with the substrate, degreasing the substrate to reduce the adhesion of impurities such as oil stains on the surface of the substrate, further improving the overall cleanliness of the substrate surface, and promoting the bonding stability between the coating and the substrate, and then etching the substrate to remove the oxide film and rust products on the surface of the substrate, further improving the bonding performance between the substrate and the coating; In the present application, the electroplating solution is a persulfate-chloride system combined to prepare the coating, and obtain a Ni-Co-P coating, which has good bonding strength, wear resistance and hardness, improves the overall quality of the coating, and improves the efficiency and quality of electroplating; 2. The electroplating solution also contains a complexing agent, trisodium citrate, which can improve the coverage of the plating solution on the base layer and further promote the dispersion performance of the plating solution. Trisodium citrate can combine with nickel ions and cobalt ions to form a complex to enhance the polarization of the cathode motor, further improving the efficiency of electroplating and the stability of the coating; 3. Surfactants, thiourea and sodium propylene sulfonate are also added to the plating solution, which can reduce the surface tension of the plating solution to promote the coating effect of the plating solution on the surface of the substrate, and can promote the precipitation of hydrogen adsorbed on the cathode surface, thereby improving the smoothness of the coating surface, further improving the hardness and stability of the coating, and effectively improving the density of the coating. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the embodiments: Description of raw materials: All raw materials in the examples are commercially available; the raw materials for the substrates in the examples and comparative examples of the present application are all brass.
[0027] Example 1 Prepare degreaser: Triammonium citrate (CAS No.: 3458-72-8), sodium silicate, sodium carbonate, and emulsifier OP-10 (CAS No.: 2201101-54-2) are mixed, the concentration of triammonium citrate in the degreasing agent is 10 g / L, the concentration of sodium silicate is 10 g / L, the concentration of sodium carbonate is 10 g / L, and the concentration of emulsifier OP-10 is 2 g / L, and the degreasing agent is obtained after stirring.
[0028] 358.7 g of nickel sulfate hexahydrate (CAS No.: 10101-97-0), 28.24 g of cobalt sulfate heptahydrate (CAS No.: 10026-24-1), 33.06 g of sodium hypophosphite (CAS No.: 7681-53-0), 120 g of trisodium citrate (CAS No.: 68-04-2), 60 g of boric acid, 40 g of sodium chloride, 160 g of complexing agent, 0.18 g of surfactant, 0.28 g of thiourea (CAS No.: 62-56-6), 0.5 g of sodium propylene sulfonate (CAS No.: 2495-39-8) and 1199.04 g of deionized water were mixed and stirred to obtain an electroplating solution.
[0029] The surfactant is sodium dodecyl sulfate (CAS No.: 151-21-3), and the complexing agent is trisodium citrate (CAS No.: 68-04-2).
[0030] Electroplating process: (1) Mechanically polishing the surface of the substrate using 600-mesh, 800-mesh, and 1000-mesh sandpaper in sequence to remove scratches and rust spots on the surface of the substrate, making the surface of the substrate smooth and flat; (2) The polished substrate is completely immersed in a 70° C. degreasing agent to clean the surface of the substrate so as to remove the oil stains on the surface of the substrate; (3) The degreased substrate was completely immersed in a 200 g / L hydrochloric acid aqueous solution and maintained at 25° C. for 1 min to remove the oxide film and rust products on the surface of the substrate; (4) The plating solution was heated to 55°C in a water bath and kept stable. The substrate was completely immersed in the plating solution. The anode and cathode were inserted into the plating solution and connected to a power source. The current density was set to 2A·dm -2 , electroplating was carried out for 48 minutes. After the electroplating was completed, the substrate was taken out, rinsed with deionized water to remove the residual plating solution, and then the surface was wiped with alcohol and dried at 70°C to complete the electroplating.
[0031] Example 2 Prepare degreaser: Triammonium citrate, sodium silicate, sodium carbonate and emulsifier OP-10 were mixed, the concentration of triammonium citrate in the degreasing agent was 10 g / L, the concentration of sodium silicate was 10 g / L, the concentration of sodium carbonate was 10 g / L, and the concentration of emulsifier OP-10 was 2 g / L, and the degreasing agent was obtained after stirring.
[0032] 365.98 g of nickel sulfate hexahydrate, 24.9 g of cobalt sulfate heptahydrate, 29.12 g of sodium hypophosphite, 160 g of trisodium citrate, 60 g of boric acid, 40 g of sodium chloride, 160 g of a complexing agent, 0.22 g of a surfactant, 0.32 g of thiourea, 0.7 g of sodium propylene sulfonate and 1158.76 g of deionized water were mixed, and stirred to obtain an electroplating solution.
[0033] Wherein, the surfactant is sodium dodecyl sulfate and the complexing agent is trisodium citrate.
[0034] Electroplating process: (1) Mechanically polishing the surface of the substrate using 600-mesh, 800-mesh, and 1000-mesh sandpaper in sequence to remove scratches and rust spots on the surface of the substrate, making the surface of the substrate smooth and flat; (2) The polished substrate is completely immersed in a 70° C. degreasing agent to clean the surface of the substrate so as to remove the oil stains on the surface of the substrate; (3) The degreased substrate was completely immersed in a 300 g / L hydrochloric acid aqueous solution and maintained at 25° C. for 3 min to remove the oxide film and rust products on the surface of the substrate; (4) The plating solution was heated to 65°C in a water bath and kept stable. The substrate was completely immersed in the plating solution. The anode and cathode were inserted into the plating solution and connected to a power source. The current density was set to 3.5 A·dm -2 , electroplating was carried out for 52 minutes. After the electroplating was completed, the substrate was taken out, rinsed with deionized water to remove the residual plating solution, and then the surface was wiped with alcohol and dried at 70°C to complete the electroplating.
[0035] Example 3 Prepare degreaser: Triammonium citrate, sodium silicate, sodium carbonate and emulsifier OP-10 were mixed, the concentration of triammonium citrate in the degreasing agent was 10 g / L, the concentration of sodium silicate was 10 g / L, the concentration of sodium carbonate was 10 g / L, and the concentration of emulsifier OP-10 was 2 g / L, and the degreasing agent was obtained after stirring.
[0036] 362.58 g of nickel sulfate hexahydrate, 26.46 g of cobalt sulfate heptahydrate, 29.12 g of sodium hypophosphite, 140 g of trisodium citrate, 60 g of boric acid, 40 g of sodium chloride, 160 g of a complexing agent, 0.2 g of a surfactant, 0.3 g of thiourea, 0.6 g of sodium propylene sulfonate and 1178.9 g of deionized water were mixed, and stirred to obtain an electroplating solution.
[0037] Among them, the surfactant is sodium dodecyl sulfate and the complexing agent is trisodium citrate.
[0038] Electroplating process: (1) Mechanically polishing the surface of the substrate using 600-mesh, 800-mesh, and 1000-mesh sandpaper in sequence to remove scratches and rust spots on the surface of the substrate, making the surface of the substrate smooth and flat; (2) The polished substrate is completely immersed in a 70° C. degreasing agent to clean the surface of the substrate so as to remove the oil stains on the surface of the substrate; (3) The degreased substrate was completely immersed in a 250 g / L hydrochloric acid aqueous solution and maintained at 25° C. for 2 min to remove the oxide film and rust products on the surface of the substrate; (4) The plating solution was heated to 60°C in a water bath and kept stable. The substrate was completely immersed in the plating solution. The anode and cathode were inserted into the plating solution and connected to a power source. The current density was set to 2.8 A·dm -2 , electroplating is carried out for 50 minutes. After the electroplating is completed, the substrate is taken out, rinsed with deionized water to remove the residual plating solution, and then the surface is wiped with alcohol and dried at 70°C to complete the electroplating.
[0039] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing the electroplating solution, 345.12 g of nickel sulfate hexahydrate, 34.52 g of cobalt sulfate heptahydrate, and 40.36 g of sodium hypophosphite are added.
[0040] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing the electroplating solution, 366.92 g of nickel sulfate hexahydrate, 24.46 g of cobalt sulfate heptahydrate, and 28.62 g of sodium hypophosphite are added.
[0041] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that the temperature during electroplating in Example 6 is 50°C.
[0042] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that the temperature during electroplating in Example 7 is 70°C.
[0043] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that the current density during electroplating in Example 8 is 1.5A·dm -2 .
[0044] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that the current density during electroplating in Example 9 is 4A·dm -2 .
[0045] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that the electroplating time in Example 10 is 40 minutes.
[0046] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that the electroplating time in Example 11 is 60 minutes.
[0047] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that the amount of sodium dodecyl sulfate added to the electroplating solution is 0.14 g.
[0048] Embodiment 13 Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that the amount of sodium dodecyl sulfate added to the electroplating solution is 0.26 g.
[0049] Embodiment 14 Example 14 is based on Example 3. The difference between Example 14 and Example 3 is that the amount of thiourea added to the electroplating solution is 0.24 g.
[0050] Embodiment 15 Example 15 is based on Example 3. The difference between Example 15 and Example 3 is that the amount of thiourea added to the plating solution is 0.36 g.
[0051] Example 16 Example 16 is based on Example 3. The difference between Example 16 and Example 3 is that the amount of sodium propylene sulfonate added to the plating solution is 0.4 g.
[0052] Embodiment 17 Example 17 is based on Example 3. The difference between Example 17 and Example 3 is that the amount of sodium propylene sulfonate added to the plating solution is 0.8 g.
[0053] Embodiment 18 Example 18 is based on Example 3. The difference between Example 18 and Example 3 is that the surfactant is hexadecyltrimethylammonium bromide (CAS No.: 57-09-0).
[0054] Embodiment 19 Example 19 is based on Example 3. The difference between Example 19 and Example 3 is that the surfactant is triethanolamine (CAS No.: 102-71-6).
[0055] Comparative Example 1 Comparative Example 1 is based on Implementation 3, and no grinding process is performed in Comparative Example 1.
[0056] Comparative Example 2 Comparative Example 2 is based on Example 3, and no degreasing treatment is performed in Comparative Example 2.
[0057] Comparative Example 3 Comparative Example 3 is based on Example 3, and no etching treatment is performed in Comparative Example 3.
[0058] Performance testing The following performance tests were performed on the samples of Examples 1-16 and Comparative Examples 1-3: (1) Hardness test The hardness of the coating was tested using a Vickers hardness tester with a load of 500g and a duration of 10s. During the test, the coating was placed on a stage and the four corners and the center of the coating were tested. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.
[0059] (2) Corrosion resistance test The porosity of the sample coating was measured using the filter paper method. The composition of the filter paper method was 20 g / L potassium ferrocyanide and 10 g / L sodium chloride. The filter paper soaked with the above composition was fully attached to the coating for 10 minutes, the filter paper was removed and dried, the number of blue spots was counted, and the porosity was calculated: Porosity = n / A (cells / cm 2 ) Where n is the number of blue spots (pcs); A is the sample area (cm 2 ) Each sample was tested 3 times, the average value was taken, and the test results were filled in Table 1.
[0060] (3) Coating deposition rate The deposition rate of the coating is determined by the difference in the mass of the sample before and after electroplating. The deposition rate is calculated as follows: V=(m 2 -m 1 ) / At Where V represents the deposition rate (g·cm -2 ·h -1 ; where h is the electroplating time)m 1 Indicates the mass of the substrate before electroplating; m 2 The quality of the substrate after surface electroplating; A represents the area of the electroplating area; after measurement, fill in the results in Table 1.
[0061] Table 1 Performance test results of Examples 1-16 and Comparative Examples 1-3 Data analysis Combined with Table 1, it can be seen that the hardness of Examples 1-3 is 380 or above, indicating that the coating prepared by the electroplating process of the present application has good hardness; the porosity of Examples 1-3 is 0.34 or below, indicating that the coating prepared by the electroplating process of the present application has good corrosion resistance; the deposition rate of Examples 1-3 is 0.026 g·cm -2 ·h -1 The above indicates that the plating rate of the coating prepared by the electroplating process of the present application is improved.
[0062] In Example 4 and Example 5, when preparing the electroplating solution, the mass ratios of nickel sulfate hexahydrate, cobalt sulfate heptahydrate and sodium hypophosphite are not within the range specified in the present application. When the content of nickel sulfate hexahydrate is too little, the nickel element in the coating is difficult to further increase, so the hardness and stability of the coating are reduced. At the same time, the contents of cobalt sulfate heptahydrate and sodium hypophosphite in the system are too much. Excessive concentration of sodium hypophosphite will affect the stability of the system, thereby affecting the hardness of the coating. Excessive concentration of cobalt sulfate heptahydrate will make the concentration of cobalt ions in the plating solution too high, and the concentration of metal ions participating in the electrode reaction in the plating solution will increase, so that the deposition of P is affected, so the performance of Example 4 is reduced; when the content of nickel sulfate hexahydrate is too much, the Co and P in the system are reduced, affecting the stability of the coating, so the performance of Example 5 is also reduced.
[0063] The temperatures during electroplating in Examples 6 and 7 are not within the range defined in the present application. When the temperature during electroplating is too low, the ion diffusion rate in the plating solution can be further improved, the cathode electrode polarization is low, the coating deposition rate is slow, it is difficult to form crystal nuclei, and the hydrogen gas during the hydrogen evolution reaction is difficult to be discharged in time, holes appear in the coating, thereby affecting the quality of the coating; and when the temperature during electroplating is too high, the hydrogen evolution side reaction may be aggravated and the coating crystals may be coarse, so the performance of Examples 6 and 7 are both reduced.
[0064] The current density during electroplating in Example 8 and Example 9 is not within the range specified in the present application. When the current density is too small, the polarization effect of the cathode is small, and it is more difficult to form crystal nuclei on the cathode surface, which reduces the stability and quality of the prepared electroplating layer. When the current density is too large, the density of the coating is affected, thereby affecting the quality of the electroplating layer. Therefore, the performance of Example 8 and Example 9 is reduced.
[0065] The electroplating time in Example 10 and Example 11 is not within the range specified in the present application. When the electroplating time is too short, it is difficult for the coating to completely cover the substrate, the protection performance of the substrate is reduced, and the uniformity is reduced, affecting the stability and quality of the coating; when the electroplating time is too long, the ion concentration of the plating solution decreases with time, the deposition rate of the coating decreases, and the stability of the coating is affected, so the performance of Example 10 and Example 11 is reduced.
[0066] The addition amount of sodium dodecyl sulfate in Example 12 and Example 13 is not within the range specified in the present application. When the content of sodium dodecyl sulfate is too little, it is difficult to further improve the porosity of the coating surface and the stability is difficult to improve; when the content of sodium dodecyl sulfate is too much, a large amount of surfactants in the plating solution agglomerate to form micelles, affecting the stability of the coating. Therefore, the performance of Example 12 and Example 13 are both reduced.
[0067] The amount of thiourea added in Example 14 and Example 15 is not within the range specified in the present application. When the amount of thiourea added is too little, it is difficult to further improve the porosity of the coating, and it is difficult to further enhance the promoting effect on the deposition of the coating. When the amount of thiourea added is too much, it will also affect the stability of the coating, and the performance of Example 14 and Example 15 will both decline.
[0068] The addition amounts of sodium allyl sulfonate in Examples 16 and 17 are not within the range defined in the present application. When the addition amount of sodium allyl sulfonate is too small, the hardness improvement effect of the coating is difficult to be further improved, which affects the overall performance of the coating. When the addition amount of sodium allyl sulfonate is too large, the stability of the plating solution system is affected, and thus the hardness and other properties of the coating are reduced.
[0069] In Example 18 and Example 19, the surfactant is replaced. When the surfactant is replaced with hexadecyltrimethylammonium bromide or triethanolamine, the hardness and glossiness of the coating are reduced, making it difficult to achieve better bonding between the coating and the substrate. At the same time, the corrosion resistance of the coating is affected. Therefore, the performance of Example 18 and Example 19 is reduced.
[0070] In Comparative Example 1, the substrate was not polished, in Comparative Example 2, the substrate was not degreased, and in Comparative Example 3, the substrate was not etched. The surface flatness of the substrate that was not polished, degreased, or etched was difficult to further improve, and oil, impurities, and oxide films adhered to the surface of the substrate, which reduced the bonding performance with the coating, thus affecting the overall stability of the coating. Therefore, the performance of Comparative Examples 1, 2, and 3 were all reduced.
[0071] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A highly efficient electroplating process, characterized in that: The steps include: S1. Grinding the substrate to remove debris on the surface of the substrate to make the surface of the substrate smooth; S2, degreasing the polished substrate with a degreasing agent; S3, subjecting the deoiled substrate to an erosion treatment; S4, transferring the plating solution to an electroplating tank, heating the plating solution and maintaining a stable temperature under the condition of a constant temperature water bath, immersing the etched substrate in the plating solution, and connecting a power supply for electroplating; S5. After the electroplating is completed, the substrate is taken out, and the residual plating solution on the surface of the substrate is washed, and then dried to complete the electroplating; The plating solution includes electrolytes including nickel sulfate hexahydrate, cobalt sulfate heptahydrate and sodium hypophosphite.
2. A high-efficiency electroplating process according to claim 1, characterized in that: The mass ratio of the nickel sulfate hexahydrate, the cobalt sulfate heptahydrate and the sodium hypophosphite is (12.7-14.7):1:1.
17.
3. A high-efficiency electroplating process according to claim 1, characterized in that: The current density is 2-3.5A / dm 2 .
4. The high-efficiency electroplating process according to claim 1, characterized in that: The electroplating temperature is 55-65°C.
5. The high-efficiency electroplating process according to claim 1, characterized in that: The electroplating time is 48-52 minutes.
6. A high-efficiency electroplating process according to claim 1, characterized in that: A complexing agent is also added to the electroplating solution, and the complexing agent includes trisodium citrate.
7. The high-efficiency electroplating process according to claim 1, characterized in that: The electroplating solution also contains surfactant, thiourea and sodium propylene sulfonate.
8. The high-efficiency electroplating process according to claim 1, characterized in that: The concentration of the surfactant is 0.09-0.11 g / L, the concentration of the thiourea is 0.14-0.16 g / L, and the concentration of the sodium propylene sulfonate is 0.25-0.35 g / L.
9. A high-efficiency electroplating process according to claim 8, characterized in that: The surfactant includes sodium lauryl sulfate.
10. The high-efficiency electroplating process according to claim 1, characterized in that: The degreasing agent comprises triammonium citrate, sodium silicate, sodium carbonate and an emulsifier.
Citation Information
Patent Citations
Diamond electroplating process
CN116575092A